Awareness of Ukrainian communities and enterprises about the problems of the Danube region - Tetiana Ivanova (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
The article is devoted to studying the level of awareness of Ukrainian communities and businesses about the problems of the Danube Region, which is an important environmental, economic and social factor for the country. The study includes responses of the population and entrepreneurs to important questions aimed at determining the level of awareness of the region's problems, identifying the main challenges faced by the Danube region, and evaluating initiatives and projects aimed at restoring the Danube. The scientific contribution of the article is to formulate recommendations for the development of the Danube Region. The article analyzes the respondents' views on the importance of attracting investment in infrastructure and environmental projects in the Danube Region to promote socio-economic development. The study takes into account the opportunities in the region and the issue of engaging the public and businesses to work together on the development of the Danube Region. The study also assesses the importance of Ukraine's cooperation with the European Union for the restoration and development of the Danube Region, given its geostrategic importance and potential for joint initiatives and projects. In addition, the article provides recommendations that should be developed to improve the condition of the Danube Region of Ukraine and its adjacent territories. The results of this study may be useful for further strategic decisions and improvement of living conditions in the Danube Region. This article will contribute to deepening knowledge about the current state of the Danube Region, its problems and development opportunities, opening the way for further research and joint work on solving important problems in the region. These recommendations can be offered as a basis for further elaboration of the State Strategy for the Development of the Region, which will be aimed at improving the environmental, economic and social situation in the Danube Region, and will contribute to strengthening cooperation between Ukraine and the European Union for the joint development of this important region.